Assessment of sorghum production constraints and farmer preferences for sorghum variety in Uganda: implications for nutritional quality breeding. (3rd October 2021) - Andiku, Charles; Shimelis, Hussein; Laing, Mark; Shayanowako, Admire Isaac Tichafa; Adrogu Ugen, Michael; Manyasa, Eric; Ojiewo, Chris
ABSTRACT: Sorghum [ Sorghum bicolor (L.) Moench] is the main food staple grain widely cultivated in sub-Sharan Africa including Uganda. There is a lack of current information on sorghum production constraints and varietal trait preferences in the major sorghum production areas in Uganda. Therefore, the objective of this study was to assess the sorghum production constraints and farmer preferences for sorghum variety in Uganda. A participatory rural appraisal study was undertaken in four selected sorghum production districts in Uganda (Kumi, Bukedea, Oyam and Gulu). Data were collected through surveys using semi-structured questionnaires and focus group discussion involving 128 and 55 participants, respectively. Data were subjected to parametric and non-parametric statistical analyses to draw inferences. A lack of improved sorghum varieties was the major sorghum production constraint reported by 82.8% of participants. Farmer preferred ideal sorghum varieties were short to medium plant height with high grain yield. The quality attributes mostly preferred by farmers were baking quality, nutrition, and seed colour. Farmers in the study areas mainly grew unimproved sorghum varieties with low food values. Overall, the study provides the current evidence on sorghum production constraints and farmer-preferred attributes that will guide sorghum nutritional quality breeding with farmer preferred traits.